2020
DOI: 10.3390/jcm9010189
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Viscoelastic Tests to Platelet Function

Abstract: Viscoelastic tests provide a dynamic assessment of coagulation, by exploring the time to clot formation and the clot strength. Using specific activators or inhibitors, additional factors can be explored, like the fibrinogen contribution to clot strength. Since the early days, various attempts have been done to measure platelet function with viscoelastic test. In general, the difference between the maximum clot strength and the fibrinogen contribution is considered an index of platelet contribution. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…Comparing the results from the lap-shear adhesion assay and the TEG assay showed that the stiffness of a clot was not directly correlated to its adhesive strength. For example, while platelets dramatically increased clot stiffness by approximately 16-fold, consistent with previous reports on the contribution of platelets to stiffness 21 , the clot adhesive strength to collagen was unchanged by platelets at the same concentration, and only increased by 1.5-fold at twice this concentration. This reflects the importance of platelets in clot cohesion through aggregation and binding of cells and proteins in blood 22 .…”
Section: Discussionsupporting
confidence: 90%
“…Comparing the results from the lap-shear adhesion assay and the TEG assay showed that the stiffness of a clot was not directly correlated to its adhesive strength. For example, while platelets dramatically increased clot stiffness by approximately 16-fold, consistent with previous reports on the contribution of platelets to stiffness 21 , the clot adhesive strength to collagen was unchanged by platelets at the same concentration, and only increased by 1.5-fold at twice this concentration. This reflects the importance of platelets in clot cohesion through aggregation and binding of cells and proteins in blood 22 .…”
Section: Discussionsupporting
confidence: 90%
“…When using VETs, some drawbacks have to be considered. First, these tests are generally poorly sensitive to platelet function and mild fibrinolysis disorders [96,97], and their sensitivity to fibrinogen levels is quite variable depending on the test methodology [98]. Second, even if considered as being global tests, they do not evaluate the contribution of endothelium, whose dysfunction likely contributes to COVID-19 associated hemostasis disturbances [34].…”
Section: Viscoelastic Testsmentioning
confidence: 99%
“…The significant thrombin generated by typical VET reagents leads to nearly complete platelet activation via the protease-activated receptors, bypassing other platelet activation pathways and making the assays insensitive to most platelet dysfunction (other than Glanzmann thrombasthenia) and most antiplatelet agents (other than glycoprotein IIb/IIIa inhibitors). 17 Thromboelastography with platelet mapping (TEG-PM) is a modification of the TEG system that allows assessment of platelet function. To make VET testing more sensitive to platelet dysfunction, clotting is activated without the formation of thrombin (an extremely potent platelet activator).…”
Section: Direct Assessment Of Shear Modulusmentioning
confidence: 99%
“…Low‐shear VET using standard reagents is generally insensitive to platelet function defects other than glycoprotein IIb/IIIa abnormalities such as Glanzmann thrombasthenia. The significant thrombin generated by typical VET reagents leads to nearly complete platelet activation via the protease‐activated receptors, bypassing other platelet activation pathways and making the assays insensitive to most platelet dysfunction (other than Glanzmann thrombasthenia) and most antiplatelet agents (other than glycoprotein IIb/IIIa inhibitors) 17 . Thromboelastography with platelet mapping (TEG‐PM) is a modification of the TEG system that allows assessment of platelet function.…”
Section: Introductionmentioning
confidence: 99%